Effects of maturation on the relationship between speed and endurance in circum-pubertal soccer players - Mendez-Villanueva, A. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Morphological and physiological considerations suggest that sprinting ability and endurance capacity put conflicting demands on the design of a human`s locomotor apparatus and therefore cannot be maximized simultaneously (Van Damme et al., 2002). However, in children the ability to demonstrate this specialization is less apparent (Rowland, 2002). That is, children who perform well in sprinting tasks also perform well in endurance activities. In this regard, it has been suggested that specialization into endurance or sprinting "types" occurs during late-puberty stages (Falk and Bar-Or, 1993). However, few studies have assessed these associations in children and adolescents of different maturational levels spanning a wide circum-pubertal spectrum. Moreover, the ability to demonstrate this specialization has yet to be tested in young soccer players where players are expected to be selected and/or trained to develop both qualities (i.e., speed and endurance) (Reilly et al., 2000). In the present study we aimed at determining whether maturation affects the relationship between sprinting speed and endurance in a group of circum-pubertal soccer players. Methods: Sprinting speed and endurance capacity were measured in 14 early-pubertal male soccer players (16.9 ± 0.7 yr old; mean ± SD), mid-pubertal male soccer players (14.3 ± 0.9 yr old) and 26 late-pubertal male soccer players (12.3 ± 0.7 yr old). Each player performed an incremental field test to exhaustion for the determination of maximal aerobic speed (MAS) (i.e., endurance capacity) and a 40- m running sprint test for the assessment of maximum sprinting speed (MSS). Relationships between size-corrected MSS and MAS measures were examined. Results: MSS was correlated with MAS (r = 0.66 ± 0.15; 95% confident limits, moderate to very large). The MSS/MAS ratio did not differ among the three groups; early-pubertal soccer players (1.16 ± 0.06; mean ± SD), mid-pubertal soccer players (1.18 ± 0.07) and latepubertal soccer players (1.16 ± 0.06). Discussion: Within this cohort of highly trained young soccer players, which spans a wide circum-pubertal spectrum, speed and endurance capacity coevolved. In conclusion, the development of sprint capacity appear not to be constrained by the need of endurance capacity and vice versa.